The Eurozone crisis and the future of Europe : the political economy of further integration and governance - Daianu, Daniel (New York, NY : Palgrave Macmillan, 2014)
'The authors uncover the roots of the eurozone crisis, focusing on various approaches on how it can be solved against the backdrop of a very deep financial and economic crisis and its strong social impact. They investigate the recent and future developments in the European Union building their argument on three key points. First, the fate of the eurozone underlies the future of the European Union, as any disarray at the core of the EU puts strong destabilizing forces into motion. Second, budget profligacy is far from explaining the depth of the current crisis in the eurozone; a flawed design and inadequate policy arrangements, which have invited rising imbalances among EU member states, are no less important in explaining the plight of and the disaffection in the eurozone. Third, even though the Banking Union project will provide a definitive solution to enhancing the cohesion of the eurozone, there are important technicalities and sequencing problems that still need clarification. Further policy arrangements going beyond the operations of a banking union will be needed in order to make the eurozone and EU function properly. The volume, furthermore, shows that the financial crisis complicates institutional and policy repair in the EU and the establishment of a lasting economic recovery. For economies to start to grow again on a sustainable basis there is a need for a sound financial intermediation system. Finance must be brought'back to reason' and be shed, as much as possible, of its speculative and destabilizing nature'--
Machine generated contents note: -- 1. Introduction; Daniel Daianu and Rajeesh Kumar -- 2. Overview: Analytics of the Euro Area Crisis; Carlo D'Adda and Giorgio Basevi -- PART I: ECONOMIC IMBALANCES AND THE EURO AREA CRISIS -- 3. The Diversity of Debt Crises in Europe; Jerome Stein -- 4. European Sovereign debt Crisis and the Euro'; Julius Horvath and Martin Suster -- 5. Economic Policies and the debt/GDP Constraint: The European Challenge'; Radu Vranceanu -- 6. Current Account Imbalances in the Eurozone: Causes, Remedies and the Role of the ECB; Karhans Sauernheimer -- PART II: CRISIS MANAGEMENT IN THE EURO AREA: THE INTERPLAY BETWEEN ECONOMICS AND POLITICS -- 7. The Euro Crisis and German Primacy; Jonathan Story -- 8. The Power of Ordoliberalism in the Eurozone Crisis Management; Brigitte Young -- 9. Italy and the Euro; Carlo D'Adda -- 10. Turning a Small Problem into Catastrophe: The Case of Greece; Kunibert Raffer -- 11. The Eurozone crisis. A Perspective from and Impact on Asia; Pradumna B. Rana and Michael R. Blomenhofer -- PART III: THE EURO AREA: LOOKING INTO THE FUTURE -- 12. The EMU is No One-Way-Street: Back to the Roots!; Bodo Herzog -- 13. Changing Welfare States and the Euro Crisis; Anton Hemerijck -- 14. The long Term Implications of the Euro Crisis for European Integration: A Deeper Union of Fragmentation; Francesco Nicoli and Fabian Zuleeg -- 15; The Euro Area : Repairing A Flawed Design and Its Policy Arrangements; Daniel Daianu -- 16. Afterword: Summing up: The Crisis and Europe's Future; Daniel Daianu and Rajeesh Kumar.
Includes bibliographical references (pages 284-299) and index.
Keywords: Global Financial Crisis, 2008-2009 -- Political aspects -- European Union countries; Financial crises -- European Union countries; Eurozone; Monetary policy -- European Union countries; European Union countries -- Economic conditions -- 21st century; European Union countries -- Economic policy